Diamond—the ultimate material for exploring physics of spin-defects for quantum technologies and diamondtronics. (18th August 2022) - Das, Dhruba; Raj, Rahul; Jana, Jayanta; Chatterjee, Subhajit; Ganapathi, K L; Chandran, Maneesh; Ramachandra Rao, M S
Abstract: Diamond due to its outstanding optical, electrical, mechanical and thermal properties finds an important place in electronic, opto-electronic and quantum technologies. Recent progresses showing superconductivity in diamond by boron doping has opened up many avenues including its applications in SQUID devices especially with polycrystalline diamond films. Granular boron doped diamond films find applications in quantum inductance devices where high surface inductance is required. Particularly important are the defect centers in diamond like nitrogen-vacancy (N-V), silicon vacancy (SiV) and other color centers which are ideal candidates for next generation quantum hardware systems. For efficient device applications, an indispensable need remains for a substitutional donor in diamond lattice that yields a lower thermal activation energy at room temperature. In this review, a comprehensive summary of research and the technological challenges has been reported including some of the results on nitrogen doping in polycrystalline diamond to understand the transport phenomenon emphasizing on its possible future applications.